Generasi Z: Pengaruh Kualitas Layanan, Brand Image, Dan Label Halal Terhadap Keputusan Pembelian Produk Mixue - Nadiya, Tsabita Izzatun; Lailatur Rohmah; Elvina Assadam; Farokhah Muzayinatun Niswah; Faricha Maf’ula (FEB Universitas Muhammadiyah Jakarta, 2025)
As a Muslim, it is an obligation to consume products that are definitely halal, regardless of whether the product is viral or not. Viral products, especially food and beverage, are an attraction for the public, especially Z generation who tend to FOMO (Fear Of Missing Out), such as Mixue. This study aims to determine the effect of service quality, brand image, and halal labels on purchasing decisions for Mixue products in Lamongan Regency on Z generation. This study is a quantitative study with the Multiple Linear Regression analysis method. The number of samples in this study was 100 respondents with a purposive sampling technique. The criteria for respondents in this study were generation Z who live in Lamongan. The results of the study showed that service quality and brand image partially influenced the purchasing decision for Mixue in Lamongan Regency on Z generation, while the halal label had no effect. Simultaneously, service quality, brand image, and halal labels influenced the purchasing decision for Mixue products in Lamongan Regency on Z generation. Keyword : service quality, brand image, halal label, purchasing decision, Mixue